2 - Formulating Higher Education Policies in Africa: The Pressure from External Forces and the Neoliberal Agenda: Birgit Brock-Utne - Birgit Brock-Utne (Journal of Higher Education in Africa, 2003)
This article analyzes the higher educational policies made for Sub-Saharan Africa by the World Bank and portrays its hostile attitude towards higher education development on the sub continent. Though an organization such as UNESCO holds up the Universal Declaration of Human Rights that states “higher education shall be accessible to all, on the basis of merit,” the Bank insists on what it calls diversification of funding and “cost sharing”. The ramifications of these policies both at individual and institutional level are discussed. Some recent documents from the Bank now recognize the importance of the sector in Africa without, however, any apologies for decades of neglect. Despite increased emphasis on the sector, the basic tenets, such as more cost sharing and more privatisation largely remain. Furthermore, the article discusses language issues in African universities and calls for the need to nurture local knowledge development. The article underscores the great need for an education that is of Africa and for Africa.